The Influence of Social Media Marketing and Online Customer Reviews on Instagram on Consumer's Interest in Buying Ichiban Sushi through the @ichibansushi_id Account: Pengaruh Social Media Marketing dan Online Customer Review pada Instagram terhadap Minat Beli Konsumen Ichiban Sushi Melalui Akun @ichibansushi_id - Silvynna Sasikirana Ramadhan; Fortuna Zain Hamid; Nidia Sofa (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2023)
This study aims to determine and analyze the influence of social media marketing and online customer reviews on Instagram on consumer buying interest in Ichiban Sushi through the @ichibansushi_id account. The research method used in this research is quantitative. The population in this study were female and male consumers, using a non-probability sampling technique with a purposive sampling method and determining the number of samples using the Slovin formula calculation results in as many as 100 respondents. The data collection technique used a questionnaire and a literature study. The data analysis technique employed a validity test, classical assumption test, multiple linear regression test, partial significance test T (T statistic test), simultaneous significance test F (F statistic test), and coefficient of determination test using SPSS version 26 for windows. Based on the T-test result, the social media marketing variable significantly affects consumer buying interest with a value of t-count > t-table of 3,211. At the same time, the online customer review variable has an effect and is significant on consumer buying interest with a value of t-count > t-table of 6,809. Based on the results of the F statistical test, the variables of social media marketing and online customer review have a simultaneous effect on consumer buying interest. The coefficient of determination obtained an R-value of 68,8% indicates that of consumer buying interest is influenced by the independent variables of social media marketing and online customer review. The other 31,2% are influenced by other variables not examined in this study. Keywords: Social Media Marketing, Online Customer Review, Consumer Buying Interest.